2014
DOI: 10.1063/1.4883501
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown mechanisms and reverse current-voltage characteristics of organic bulk heterojunction solar cells and photodetectors

Abstract: We investigate the reverse current-voltage characteristics and breakdown mechanisms of organic bulk heterojunction solar cells and photodetectors. Dark current and photo current measurements at different temperatures indicate that tunneling is the dominant mechanism at high reverse voltage. A band-to-band tunneling model that accommodates either Gaussian or exponential-parabolic density of states distributions is developed and used for simulations. At high reverse bias, the model explains the observed breakdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Instead, in Ref. [38], it was reported that the tunneling current can be the major effect in the reverse bias. Therefore, we believe impact ionization may not play a major role in the reverse bias for P3HT:PCBM organic solar cells.…”
Section: Figure 4 Tablementioning
confidence: 99%
See 3 more Smart Citations
“…Instead, in Ref. [38], it was reported that the tunneling current can be the major effect in the reverse bias. Therefore, we believe impact ionization may not play a major role in the reverse bias for P3HT:PCBM organic solar cells.…”
Section: Figure 4 Tablementioning
confidence: 99%
“…Although the reverse current of P3HT:PCBM organic solar cells could increase rapidly beyond a specific electric field value (larger than 5x10 7 V/m according to Ref. [38]), there is still no report on associating such current breakdown to the carrier avalanche. Instead, in Ref.…”
Section: Figure 4 Tablementioning
confidence: 99%
See 2 more Smart Citations
“…We attribute the excess LFN in the reverse bias from devices annealed at While the improved morphology as a result of higher annealing temperature should yield less pronounced trap-assisted tunneling, in fact, the tunneling current is also related to other factors such as the material band structure and the carrier effective mass [23], [135]. While there have been few studies on how the carrier effective mass changes with the annealing temperature, it is observed that thermal annealing modifies the band structure of P3HT:PCBM films manifested by the red-shift in the absorption spectrum [126].…”
Section: Figure 54: the Circuit Diagram For The Low-frequency Noise mentioning
confidence: 99%